2016
DOI: 10.7717/peerj.1853
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of traditional Japanese alcohol beverages on blood glucose and polysomnography levels in healthy subjects

Abstract: Background. Alcohol consumption is a lifestyle factor associated with type 2 diabetes. This relationship is reportedly different depending on the type of alcohol beverage. The purpose of this study was to examine the acute effects of traditional Japanese alcohol beverages on biochemical parameters, physical and emotional state, and sleep patterns.Methods. Six healthy subjects (three men and three women; age, 28.8 ± 9.5 years; body mass index, 21.4 ± 1.6 kg/m2) consumed three different types of alcohol beverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…It steps up triglyceride production in plasma29 and cuts down glucose consumption in peripheral tissues by targeting insulin signaling pathways and the glucose transporter 4 (GLUT4) 3,30. Parallel to our findings, Kido et al13 have reported that high intake of alcoholic beverages with a meal causes different responses in postprandial glucose and insulin concentrations. Accordingly, sake reduces the levels of lipids and glucose through modulation in TNF-α.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It steps up triglyceride production in plasma29 and cuts down glucose consumption in peripheral tissues by targeting insulin signaling pathways and the glucose transporter 4 (GLUT4) 3,30. Parallel to our findings, Kido et al13 have reported that high intake of alcoholic beverages with a meal causes different responses in postprandial glucose and insulin concentrations. Accordingly, sake reduces the levels of lipids and glucose through modulation in TNF-α.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have shown that sake is made up of water and ethanol, D -glucose, ethyl α- D -glucoside, glycerol, organic acids, and amino acids 12. Kido et al13 stated that high intake of alcoholic beverages with a meal may cause different responses in postprandial glucose and insulin concentrations. Studies showed that Japanese sake yeast enriched in adenosine analogs activates A2a receptors and its supplementation improved sleep quality 14.…”
Section: Introductionmentioning
confidence: 99%
“…The study characteristics for the twenty-two studies are provided (Table 3). Nine studies (30)(31)(32)(33)(34)(35)(36)(37)(38) were excluded and justification for exclusion is provided in online Supplementary Table S1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The study was conducted at the Clinical Trials Unit (CTU) of Oita University Hospital. In each period of allocation, the entire dose of 0.33 g/kg of barley shochu or water at room temperature was consumed over ~10 min 3,8,11 . Measurements of ethanol and acetaldehyde concentrations in exhaled breath, the psychomotor test, and visual analogue scale (VAS) self‐ratings were conducted before drinking and at 15, 30 min, and 1, 1.5, 2, 3, 4, 6, 8, 10, and 12 h after drinking.…”
Section: Methodsmentioning
confidence: 99%
“…Sustained exposure to acetaldehyde, the major metabolite of ethanol, may influence psychomotor performance even after the breath ethanol level significantly drops several hours following ethanol consumption. However, there are only a few reports, including our own, on genotype‐specific differences in the persistence of ethanol or acetaldehyde in exhaled breath for longer than 6 h after drinking 3,7–11 . Ethanol concentration in exhaled breath is measured to detect drunk driving, and the standard level for safe driving in Japan is 0.15 mg/ml or lower.…”
Section: Introductionmentioning
confidence: 99%